Geological Sites Supporting the Sustainable Development Goals of the UN 2030 Agenda: A Survey on the North Coast of São Paulo, Brazil - Laíza Lauriano; Debora Queiroz; Maria Garcia (Geoconservation Research)
An essential component for sustaining biodiversity and providing natural resources for society is the management of geodiversity, as represented by the geoheritage of a region, comprising a collection of geosites. In nature conservation planning, the UN 17 Sustainable Development Goals (SDGs) provide an excellent framework for both the private and public sectors. The north coast of the state of São Paulo, Brazil is an area widely used for tourism, with critical problems related to mainly anthropogenic degradation of nature. Forty-three geosites that show important records of regional geology were analyzed for their potential support in achieving the UN 17 SDG and 169 targets. Using Essential Geodiversity Variables (EGVs), our results indicate that, from the 17 SDGs, 13 could benefit directly from actions involving local geodiversity. The relative performance of the geosites in terms of the number of targets for each SDG ranges from 7.7 to 50%. We show that geodiversity plays a fundamental role in contributing to sustainable development and has great potential to influence public policies. In addition, our work can serve as an inspiration for studies involving ecosystem services and encourage greater participation of the local community in nature conservation actions with the sustainable use of geodiversity.